AHIMSA AND ĀNṚŚAṂSYA DHARMA FROM THE MAHABHARATA FOR A SUSTAINABLE UNIVERSE - Gorai, Bithika; Dwivedi, Rajiv Ranjan (Journal of Dharma, 2022)
The article explores and elucidates two parama (greatest) dharmas from the Mahabharata, Ānṛśaṃsya (absence of cruelty, vileness, and treachery) and Ahimsa (non-violence), as a means to promote the goal for a sustainable way of living in the world which faces the challenges of a narrow anthropocentric worldview. Having investigated the intricacies involved in violence, non-violence, and just violence with illustrations from the Mahabharata, the paper delves into the principle of anṛśaṃsya and its practical applicability in real life. The ethical practice of Ānṛśaṃsya in action, if transmitted from individual to the community, can bring positive changes in the functioning of the world, ensuring the welfare and sustainable prosperity for all.